Gendered Pathways in Design Education: Findings from a Public University in India - Dhaundiyal, Dhriti; Dhaundiyal, Shruti (Design and Technology Education: An International Journal, 2022)
The substantive aims of education include equitable learning, which stands for equitable gender access to preferred learning and choice within. These substantive aims can be furthered by pursuing certified vocational courses that equalize the presence of males and females in the job market through competitive skill sets. Design education in India was imagined as a composite field encompassing both technical studies and social sciences, and it was concentrated in metropolitan cities and technical institutions. It has now slowly spread to newer cities and more disciplinarily diverse institutions. Our research posits that the current unstructured growth of design education leads to a lack of emphasis on substantive outcomes. Rather, there is a focus on education for the sake of acquiring a certified competitive skill. We further analyze the distinction that has emerged between 'industrial' and 'communication' domains within design. This distinction is visible in the twinning of industrial design with engineering and architecture, while communication design is seen closer to fine arts and aesthetics as a stream not requiring technical expertise. This perception has precipitated a trend of gendered pathways in design education. This study used an exploratory approach to analyze five years of admissions data from the design department of a public university in a Tier 2 town in India, followed by semi-structured interviews with students and alumni. We found evidence to support the thesis of gendered pathways, attributed to factors like conventions of society, perceived safety, learning styles, curricular expenditure, and course briefs.